2014
DOI: 10.3141/2464-18
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Course Study of Driver Detection of Pedestrians beyond Flashing Beacons within Sign Assembly

Abstract: This study evaluated the effect of yellow rapid flashing beacon characteristics on the ability to detect objects located behind a sign during a closed-course driving study sponsored by FHWA. For the analysis focusing on object detection distance, the results indicated that certain study assemblies were associated with shorter object detection distances. During the day, the object detection distance was shorter for objects behind an assembly with two rectangular beacons below the sign (R-B), as opposed to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A closed-course study conducted for FHWA investigated driver ability to detect an object (e.g., box, trash can, pedestrian) about 3 ft beyond an assembly for different combinations of beacon shape (i.e., circular or rectangular), size (i.e., 8 or 12 in. for the circular shape), and placement (i.e., above or below the flashing sign) (5). The study showed that certain assemblies were associated with shorter object-detection distances, which are not desirable.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…A closed-course study conducted for FHWA investigated driver ability to detect an object (e.g., box, trash can, pedestrian) about 3 ft beyond an assembly for different combinations of beacon shape (i.e., circular or rectangular), size (i.e., 8 or 12 in. for the circular shape), and placement (i.e., above or below the flashing sign) (5). The study showed that certain assemblies were associated with shorter object-detection distances, which are not desirable.…”
mentioning
confidence: 87%
“…Toward the conclusion of the closed-course study, cities were sought to participate in the open-road research; city representatives were contacted and requests were made at professional society meetings (5). Four cities volunteered to participate: Milwaukee, Wisconsin; Flagstaff, Arizona; Austin, Texas; and College Station, Texas.…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation